A novel combination of niraparib and anlotinib in platinum-resistant ovarian cancer: Efficacy and safety results from the phase II, multi-center ANNIE study. (December 2022) - Liu, Guochen; Feng, Yanling; Li, Jing; Deng, Ting; Yin, Aijun; Yan, Lei; Zheng, Min; Xiong, Ying; Li, Jundong; Huang, Yongwen; Zhang, Chuyao; Huang, He; et al.
Summary: Background: Patients with platinum-resistant recurrent ovarian cancer (PROC) face poor prognosis and limited treatment options. Single-agent antiangiogenics and poly (ADP-ribose) polymerase (PARP) inhibitors both show some activities in platinum-resistant diseases. The ANNIE study aimed to evaluate the efficacy and safety of the novel combination of the PARP inhibitor niraparib and the antiangiogenic anlotinib in patients with PROC. Methods: ANNIE is a multicentre, single-arm, phase 2 study (ClinicalTrials.gov identifier NCT04376073 ) conducted at three hospitals in China. Eligible patients had histologically confirmed epithelial ovarian, fallopian tube, or primary peritoneal cancer that recurred within 6 months of last platinum-based chemotherapy. Patients with prior PARP inhibitor exposure were excluded. The enrolled patients received oral niraparib 200 mg or 300 mg (baseline body weight-directed) once daily continuously and anlotinib 10 mg (12 mg before protocol amendment) once daily on days 1–14 of each 21-day cycle until disease progression or intolerable toxicity. The primary endpoint was objective response rate (ORR). Findings: Between May 22, 2020, and April 22, 2021, 40 patients were enrolled and treated. Thirty-six patients underwent post-baseline tumour assessments. By data cut-off (January 31, 2022), median follow-up was 15.4 months (95% CI 12.6–17.7). Intention-to-treat ORR was 50.0% (95% CI 33.8–66.2), including one complete response and 19 partial responses. Median (95% CI) progression-free survival and overall survival were 9.2 months (7.4–11.9) and 15.3 months (13.9–not evaluable), respectively. Drug-related, grade ≥3 TEAEs were reported in 26 (68%) patients. There were no treatment-related deaths. Interpretation: Niraparib plus anlotinib showed promising antitumour activity in patients with PROC. This oral combination warrants further investigation as a potential novel, convenient treatment option for patients with PROC. Funding: Zai Lab (Shanghai) Co., Ltd ; Jiangsu Chia Tai-Tianqing Pharmaceutical Co., Ltd ; the National Natural Science Foundation of China (No. 82102783 ).